Exploring the Impact of Committee Structure and Composition on Corporate Governance Practices - Asri, Marselinus (Advances in Managerial Auditing Research, 2024)
The purpose of this research is to investigate the impact of committee structure and composition on corporate governance practices. Employing a qualitative approach, a comprehensive literature review was conducted to synthesize theoretical perspectives, empirical findings, and practical insights on the subject matter. The findings reveal significant implications for corporate governance practices, particularly concerning audit committees and nominating/governance committees. Audit committees with independent directors and financial expertise are found to be more effective in overseeing financial reporting and internal controls, as mandated by regulatory requirements such as the Sarbanes-Oxley Act. Similarly, nominating and governance committees that prioritize diversity, including gender, ethnicity, age, and cognitive dimensions, contribute significantly to decision-making quality and stakeholder representation. The implications of these findings extend to theory development, policy formulation, and managerial decision-making in corporate governance contexts. Organizations can enhance their governance practices by ensuring the presence of independent and diverse committee members, complying with regulatory requirements, and fostering inclusive decision-making environments. Embracing diversity within governance structures is essential for promoting innovation, resilience, and long-term sustainability. The research underscores the importance of addressing challenges related to recruitment, retention, diversity promotion, and regulatory compliance to achieve optimal committee effectiveness. Future research directions include exploring innovative approaches to enhancing committee effectiveness, leveraging technology-enabled recruitment platforms, implementing diversity training programs, and conducting longitudinal studies to assess the long-term effects of committee configurations on organizational performance and sustainability